A Contextualized Reinforcement and Intervention Program in Mathematics for Selected Senior High School Students - Combo, John Edward A.; Olino, Ma. Victoria D.; Rivas, Ana Maria G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This action research evaluates the effectiveness of a contextualized reinforcement and intervention program in Mathematics for selected Senior High School (SHS) students at Maximo L. Gatlabayan Memorial High School (MLGMNHS). The participants were students who previously scored below 75% of the highest possible score in Mathematics examinations and/or demonstrated low performance in the Learning Outcomes Assessment (LOA) or Individual Monitoring Learning Plan (ILMP). They were identified by their subject teachers and validated through a pre-test. To assess the program’s impact, the participants took a teacher-designed post-test, and the results were analyzed to determine significant differences in their performance before and after the intervention. Additionally, some students were interviewed to gain insights into their experiences and the challenges they faced throughout the program. Findings indicate that implementing structured intervention programs in Mathematics significantly enhances students’ mathematical knowledge and overall performance. Therefore, schools should invest more effort in sustaining and improving such programs to maximize their impact on student learning outcomes.